The Expression of Epidermal Growth Factor (EGF) and its Receptor (EGFR) During Post‐Natal Testes Development in the Yak. Issue 6 (26th September 2014) - Pan, Y; Cui, Y; Yu, S; Zhang, Q; Fan, J; Abdul Rasheed, B; Yang, K
Contents Growth factors play critical role in cell proliferation, regulate tissue differentiation and modulate organogenesis. Several growth factors have been identified in the testes of various mammalian species in last few years. In present investigation, the objective was to determine the expression of epidermal growth factor (EGF) and the epidermal growth factor receptor (EGFR) in yak testicular tissue by relative quantitative real time polymerase chain reaction (RT‐PCR), Western blot (WB) and immunohistochemistry (IHC) from mRNA and protein levels. The testicular tissues were collected from male yak at 6 and 24 months old. Results of RT‐PCR and WB showed that the expression quantity of EGF and EGFR at 24 months of age was higher than at 6 months, and the increase rate of EGFR on mRNA and protein levels was higher than the increase rate EGF during post‐natal testes development. Positive staining for EGF and EGFR was very low and mainly localized to Leydig cells testes at 6 months of age with immunohistochemistry, and seminiferous tubules were not observed. At 24 month of age, both the EGF and EGFR could be detected in Leydig cells, peritubular myoid cells, sertoli cells and germ cells of the yak testes. However, EGF and EGFR were localized to preferential adluminal compartment and basal compartment in the seminiferous tubules, respectively. In conclusion, the findings in present studies suggest that EGF and EGFR as important paracrine and/or autocrine regulators in yak testes development and spermatogenesis.